Designing teaching strategy to enhance student learning (II) - Siddiqui, Salim; Yeo, Shelley; Zadnik, Marjan (Curtin University of Technology, 2002)
This study investigates how the prior knowledge of the students can be used to develop an effective teaching and learning strategy. First - year university science students come from a variety of teaching and learning cultures with a wide range of academic abilities. Moreover many studies have shown that science students hold a variety of alternative conceptions that are hard to change. These combining factors pose a daunting challenge for the instructor to teach such a group of varying abilities and mixed conceptions. A traditional mode of teaching in many cases is not suitable and may result in a high drop out rate. Before embarking on a full teaching program, it is therefore, useful to develop a teaching and learning strategy that is suitable for the whole class. In this paper we will discuss the outcome of two years of study for two different groups of students.